Islamic Economic Perspective on Islamic Bank Employee Loyalty: The Role of Competence, Motivation, and Reputation - Cindi Safitri; Any Eliza; Is Susanto (Department of Islamic Banking, 2026)
Purpose – This study aims to analyze the influence of competence, motivation, and reputation of the company on the loyalty of employees of Bank Syariah Indonesia (BSI) KCP Belitang Sudirman from the perspective of Islamic Economics. Methodology – This study uses a quantitative approach, grounded in positivism, employing census sampling (total sampling) of 67 staff and leaders at Bank Syariah Indonesia (BSI) KCP Belitang Sudirman as respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Findings – The results showed that only the motivation variable had a positive and significant effect on loyalty, whereas the company's competence and reputation did not have a significant effect. This indicates that employee loyalty is driven more by the fulfillment of material and spiritual needs (motivation) than by technical ability or the institution's big name. Implications– This finding suggests that management needs to strengthen the reward system and the Islamic work environment to maintain employee compliance with the contract, given that, from an Islamic perspective, loyalty is a mandate rooted in emotional and spiritual attachment to the organization. Originality– This research contributes novelty by integrating the variables of motivation, competence, and reputation of the company in one structural model to test employee loyalty at the sub-branch office level of Islamic banking, which is analyzed comprehensively through the lens of the values of trust and sanctity of the contract from the perspective of Islamic Economics.